Total and trimester‐specific gestational weight gain and infant anthropometric outcomes at birth and 6 months in low‐income Hispanic families. Issue 3 (6th November 2019) - Deierlein, Andrea L.; Messito, Mary Jo; Katzow, Michelle; Berube, Lauren Thomas; Dolin, Cara D.; Gross, Rachel S.
Abstract: Objective: To describe total and trimester‐specific gestational weight gain (GWG) among low‐income Hispanic women and determine whether these GWG exposures are associated with infant anthropometric outcomes at birth and 6 months. Study Design: Data were from 448 mother‐infant pairs enrolled in the Starting Early child obesity prevention trial. Prenatal weights were used to calculate total GWG and 2 nd and 3 rd trimester GWG rates (kg/week) and categorized as inadequate, adequate, and excessive according to the 2009 Institute of Medicine recommendations. Multivariable linear and modified Poisson regressions estimated associations of infant anthropometric outcomes (birthweight, small‐for‐gestational age [SGA], large‐for‐gestational age [LGA], rapid weight gain, and weight‐for‐age, length‐for‐age, and weight‐for‐length z‐scores at 6 months) with GWG categories. Results: For total GWG, 39% and 27% of women had inadequate and excessive GWG, respectively. 57% and 46% had excessive GWG rates in the 2 nd and 3 rd trimesters, respectively, with 29% having excessive rates in both trimesters. Inadequate total GWG was associated with lower infant weight and length outcomes (ß range for z‐scores = −0.21 to −0.46, p < 0.05) and lower risk of LGA (adjusted Relative Risk, aRR = 0.38; 95% confidence intervals, CI: 0.16, 0.95) and rapid weight gain (aRR = 0.72; 95%CI: 0.51, 1.00). GWG rates above recommendations in the 2 nd trimester or 2 nd /3 rd trimesters were associated with greater weight outcomes at birth and 6 months (ß range for z‐scores = 0.24 to 0.35, p < 0.05). Conclusions: Counseling women about health behaviors and closely monitoring GWG beginning in early pregnancy is necessary, particularly among populations at high‐risk of obesity.